From Agents to Offices: A Case Study Examining International Business Relationships - Traverso, Pablo (2010)
The factors which contribute towards international business success in the relationship between firms located in different parts of the world have been subject to considerable scrutiny, particularly in recent years. The main purpose of this study is to critically assess the effects on business relationships when a company invests in foreign markets in order to get closer to their target customer base. We will focus on the main conduits which form a Relationship Marketing strategy. Such a strategy aims to reach the objective of a long term international business relationship between international firms. The idea of exploring this concept is based on a model, “Key Mediating Variables (KMV)” put forward in Morgan and Hunt’s (1994) study of successful relationship marketing practice. This model specifically addresses inroads to successful international business relationships. The research focuses on geographical proximity of B2B firms with reference to these determinants. Qualitative research methods are employed in this study. This is partly due to the author’s relationship with a particular firm. In addition, for the most part, having the objective of creating an evidenced discourse would serve conclusions better than the analysis of numerical data in the aforementioned context. A Chilean company called Arauco Forest Products S.A. which has invested in an interface sales subsidiary in Leiden, Holland will be the subject of the case study for this thesis. The data was gathered through semi-structured personal interviews with the different participants in this business relationship. Such a choice of qualitative data gathering technique would allow the author to guide the interview objectively, but allow for a certain freedom that could result in the teasing out of important data, which may not have come to the surface in a more rigid context. Firstly, the background of Arauco Forest Products S.A. is presented, and the market conditions of the country in which it has originated and is based, Chile are explored. Subsequently, the Key Mediating Variables of relationship marketing are considered. Next, a review of the academic literature on geographic proximity and business relationships sets the thesis in its context as well as allowing a critique on previous studies and the original thought of previous researchers on the topic. The different factors making up the KMV model are revisited in the context of the research findings in terms of how they are influenced by geographic proximity in the concluding chapter. Keywords: International Business relationships, KMV model, Geographic proximity, Relationship Marketing